2020
DOI: 10.21203/rs.3.rs-22197/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transanal Proctocolectomy and Ileal Pouch-Anal Anastomosis (Taipaa) for Ulcerative Colitis: Medium Term Functional Outcomes in a Single Centre

Abstract: Background: Transanal dissection of the rectum has been recently introduced for ileal pouch-anal anastomosis (IPAA) in UC showing promising results. Thanks to the precise identification of the rectotomy site the risk of long rectal stump is avoided, and a single stapled anastomosis is performed easily.The aim of this study is to analyze our initial experience of transanal proctocolectomy and ileal pouch-anal anastomosis (TaIPAA), considering postoperative complications and medium-term functional outcomes.Metho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Early studies have demonstrated similar or decreased postoperative morbidity in taIPAA patients compared to other MIS IPAA patients. 41 43 TaIPAA patients have comparable quality of life and bowel, urinary, and sexual function, 44 though these data are preliminary and based on small case series. Overall, it appears that taIPAA offers improved visualization and access during the low pelvic dissection, likely lower conversion rates, and similar postoperative and functional outcomes.…”
Section: Transanal Ileal Pouch Anal Anastomosismentioning
confidence: 91%
“…Early studies have demonstrated similar or decreased postoperative morbidity in taIPAA patients compared to other MIS IPAA patients. 41 43 TaIPAA patients have comparable quality of life and bowel, urinary, and sexual function, 44 though these data are preliminary and based on small case series. Overall, it appears that taIPAA offers improved visualization and access during the low pelvic dissection, likely lower conversion rates, and similar postoperative and functional outcomes.…”
Section: Transanal Ileal Pouch Anal Anastomosismentioning
confidence: 91%